Applications of solid-phase microextraction for the analysis of pesticide residues in fruits and vegetables: A review - Abdulra'uf L.B.; Chai M.K.; Tan G.H. (AOAC International, 2023)
This paper reviews the application of various modes of solid-phase microextraction (SPME) for the analysis of pesticide residues in fruits and vegetables. SPME is a simple extraction technique that eliminates the use of solvent, and it is applied for the analysis of both volatile and nonvolatile pesticides. SPME has been successfully coupled to both GC and LC. The coupling with GC has been straightforward and requires little modification of existing equipment, but interfacing with LC has proved challenging. The external standard calibration technique is widely used for quantification, while standard addition and internal or surrogate standards are mainly used to account for matrix effects. All parameters that affect the extraction of pesticide residues from fruits and vegetables, and therefore need to be optimized, are also reviewed. Details of the characteristics of analytical procedures and new trends in fiber production using sol-gel technology and molecularly imprinted polymers are discussed.